Long Non-coding RNAs in Pathogenesis of Neurodegenerative Diseases - Zhou, Shiyue; Yu, Xiao; Wang, Min; Meng, Yujie; Song, Dandan; Yang, Hui; Wang, Dewei; Bi, Jianzhong; Xu, Shunliang (Frontiers in Cell and Developmental Biology, 2021)
Emerging evidence addresses the link between the aberrant epigenetic regulation of gene expression and numerous diseases including neurological disorders, such as Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), and Huntington’s disease (HD). LncRNAs, a class of ncRNAs, have length of 200 nt or more, some of which crucially regulate a variety of biological processes such as epigenetic-mediated chromatin remodeling, mRNA stability, X-chromosome inactivation and imprinting. Aberrant regulation of the lncRNAs contributes to pathogenesis of many diseases, such as the neurological disorders at the transcriptional and post-transcriptional levels. In this review, we highlight the latest research progress on the contributions of some lncRNAs to the pathogenesis of neurodegenerative diseases via varied mechanisms, such as autophagy regulation, Aβ deposition, neuroinflammation, Tau phosphorylation and α-synuclein aggregation. Meanwhile, we also address the potential challenges on the lncRNAs-mediated epigenetic study to further understand the molecular mechanism of the neurodegenerative diseases.